2009
DOI: 10.1007/s11262-009-0408-4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of wild-type measles virus to cotton rat lung cells: E89K mutation in matrix protein contributes to its fitness

Abstract: Wild-type measles virus (wtMeV) adapted well to cotton rat lung (CRL) cells after serial passages. In order to evaluate the contributions of the individual genes of wtMeV for adaptation, whole genome sequences of the adapted and original viruses were determined and analyzed. The results showed that there were two mutations in the whole genome of the adapted virus. One mutation was located at the 265th nucleotide in the open reading frame (ORF) of the M gene, resulting in the substitution of the 89th amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…MVi/Tokyo.JPN/37.99(Y) and MVi/Tokyo.JPN/37.99(Y)C7 are genotype D3, the former is a wild-type isolate, the latter is its cell culture passaged derivative [39]. Both have identical insertions in the M 3′ UTR and identical deletions that replace 27 amino acids at the carboxyl-terminus of the F1 protein with a different sequence of 11 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…MVi/Tokyo.JPN/37.99(Y) and MVi/Tokyo.JPN/37.99(Y)C7 are genotype D3, the former is a wild-type isolate, the latter is its cell culture passaged derivative [39]. Both have identical insertions in the M 3′ UTR and identical deletions that replace 27 amino acids at the carboxyl-terminus of the F1 protein with a different sequence of 11 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the adaptation of the measles virus to cotton rats was accompanied by a single mutation in the matrix protein, and the adaptation of chimpanzee immune deficiency virus to human lymphoid tissue also was dependent on a point mutation in the gag matrix protein (35,36). The mechanisms of how the mutated matrix proteins mediated the effect on replicative fitness in a new host remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Adapted virus MV99YC7, which adapted well to CRL cells after serial passages, possesses a mutation in the M gene causing E89K substitution and one silent mutation in the L gene, as compared to the parental virus MV99Y [10]. Human PBMC were isolated from healthy adults using Ficoll-Paque PREMIUM (GE Healthcare Bio-science, Piscataway, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…It also can affect efficient growth and cell-cell fusion [8, 9]. A previous study revealed that the E89K substitution mutation in M protein plays a key role in wild-type MeV adaptation in the cotton rat and cotton rat lung (CRL) cells [10]. …”
Section: Introductionmentioning
confidence: 99%